Conservation Priority Index of species, communities, and habitats for biodiversity conservation and their management planning: A case study in Gulmarg Wildlife Sanctuary, Kashmir Himalaya - Wani, Zishan A.; Bhat, Jahangeer A.; Negi, Vikram S.; Satish, K. V.; Siddiqui, Sazada; Pant, Shreekar (Frontiers in Forests and Global Change, 2022)
The present study is an attempt to evaluate the Conservation Priority Index (CPI) of species, habitats, and communities for their conservation and management planning in the Kashmir Himalayas in India. The present study is an attempt to prioritize 361 plant species, 18 plant communities (10 within the forest zone and 08 within the alpine zone), and 07 habitats for conservation planning. Out of the total plant species recorded, 06 species were categorized as critically endangered, 20 endangered, 28 vulnerable, and 98 species to be near threatened. Amongst the forest and alpine communities, Abies pindrow community and Juniperus squamata-Rhododendron anthopogon mixed community showed the maximum CPI values. Amongst the habitats, dry habitats showed the maximum CPI in the sanctuary. The study found that the threatened species positively correlated with the native and endemic species indicating that these species were rigorously affected due to biotic and abiotic stresses. Based on the results of the present study, we propose a practical method for biodiversity conservation and management of protected areas. The approach employs a variety of qualitative and quantitative features to compute CPI in conjunction with phytosociological data. This kind of study will be immensely helpful to forest officials, policy makers, conservators, and researchers for planning better strategies to conserve and manage particular species, communities, and even habitats in protected areas.